Optimizing Assurance The risk Regulation System in Relationships. [article]. - Murray, Sandra L..
A model of risk regulation is proposed to explain how people balance the goal of seeking closeness to a romantic partner against the opposing goal of minimizing the likelihood and pain of rejection. The central premise is that confidence in a partner's positive regard and caring allows people to risk seeking dependence and connectedness. The risk regulation system consists of 3 interconnected "if-then" contingency rules, 1 cognitive, 1 affective, 1 behavioral. The authors describe how general perceptions of a partner's regard structure the sensitivity of these 3 "if-then" rules in risky relationship situations. The authors then describe the consequences of such situated "if-then" rules for relationship well-being and conclude by integrating other theoretical perspective and outlining future research directions. -- (from the author)
Keywords: Relationships; Rejection; Perceived regard; Risk; Belongingness